Discovery and Cross-Validation of Peripheral Blood and Renal Biopsy Gene Expression Signatures from Ethnically Diverse Kidney Transplant Populations - Ventura, Carlucci Gualberto (Am J Transplant, 2019)
We determined peripheral blood (PB) and biopsy (Bx) RNA expression signatures in a Brazilian and US cohort of kidney transplant patients. Phenotypes assigned by precise histology were: Acute Rejection, (AR) IFTA/Chronic Rejection (CR), excellent functioning transplants (TX), and Glomerulonephritis recurrence (GN). Samples were analyzed on microarrays and profiles from each cohort cross-validated on the other cohort with similar phenotypes. We discovered signatures for each tissue: 1) AR vs TX; 2) CR vs TX and 3) GN vs TX using the Random Forests algorithm. We validated biopsies signatures of AR vs TX (AUC 0.97) and CR vs TX (AUC 0.87). We also validated both PB and Bx signatures of AR vs TX and CR vs TX with varying degrees of accuracy. Several biological pathways were shared between AR and CR suggesting similar rejection mechanisms in these two clinical phenotypes. Thus, we identified gene expression signatures for AR and CR in transplant patients and validated them in independent cohorts of significantly different racial/ethnic backgrounds. These results reveal that there are strong unifying immune mechanisms driving transplant diseases and identified in the signatures discovered in each cohort suggesting that molecular diagnostics across populations are feasible despite ethnic and environmental differences.